SAT0271 Is there a need to include serological pattern to predict damage in patients with antiphospholipid syndrome: diaps application. (15th June 2017) - Mazilu, D; Potarniche, D; Saulescu, I; Borangiu, A; Groseanu, L; Constantinescu, C; Vlad, V; Opris, D; Balanescu, A; Predeteanu, D; Ionescu, R
Abstract : Background: Antiphospholipid syndrome (APS) is an autoimmune disease defined as the presence of antiphospholipid antibodies (aPL), at least a clinical thrombotic event and is associated with an important risk of organ damage. The new index proposed, Damage Index in patients with Thrombotic Antiphospholipid Syndrome (DIAPS) may be an useful tool to estimate cumulative damage in patients with primary and secondary APS. It includes 38 clinical items expanded to show the complexity of clinical manifestations in APS patients. Objectives: The aim of this study is to analyze the serological pattern as potential predictive factor for an increased DIAPS. Methods: All consecutive patients known with APS according to the Sapporo and/or Sydney classification criteria were included in our monocentric cohort. Data on medical history, clinical manifestations, aPL profile and medication were collected. DIAPS score was used to measure damage in each patient. The relationship between aPL profile and DIAPS score was analysed. Results: Seventy six patients with APS were included: 11 patients with primary APS, 65 patients with secondary APS. Their mean disease duration was 9.59±7.39years. The most frequent clinical manifestation from DIAPS was the peripheral vascular (deep vein thrombosis, intermittent claudication, tissue loss, vascular venous insufficiency) found in 61.8% of patients, followed by the neuropsychiatric manifestations (46.1%). The mean DIAPS score in our cohort was 4.25±3.51, not significantly different between patients with primary vs secondary APS (4.72 vs 4.16, p=0.629). Lupus anticoagulant (LA) was found in 25 patiens (32.9%), anti cardiolipin antibodies (aCL) in 49 patients (64.5%) and antibodies to β2-glycoprotein I (β2GPI) in 23 patients (30.3%). There were 36 patients known with a single positive aPL (47.4%), 27 patients (35.5%)with 2 positive aPL and only 2 patients with triple positivity. There were no significant differences regarding antibody profile between patients with primary and secondary APS. Higher values of DIAPS were seen in patients with β2GPI (p=0.042) and with positivity for 2 aPL (p=0.003). DIAPS value correlated to the presence of β 2GPI (p=0.042, R=0.233) and to positivity for two aPL (p=0.003, R=0.341). Conclusions: Our study suggests that double positivity for aPL, especially the presence of β2GPI confers an increased value of DIAPS in patients with primary and secondary APS. References: M-C Amigo et al. Development and initial validation of a damage index (DIAPS) in patients with thrombotic antiphospholipid syndrome (APS). Lupus (2015) 24, 927–934. LM Amezcua-Guerra. Improving definitions for an index of cumulative organ damage in patients with the antiphospholipid syndrome (DIAPS). Lupus (2016) 25, 671–672. Disclosure of Interest: None declared